Influences of women empowerment indices on demand for childcare services: Evidence from the Nigeria Demographic and Health Surveys - Zhou D.; Ahuru R.R.; Yan M.; Osabohien R.; Jakovljevic M. (Women's Health and Action Research Centre, 2024)
This study examined the effect of various dimensions of womens empowerment on childcare use in Nigeria, utilizing information from five rounds of the National Demographic and Health Surveys. The analysis made use of both binary and multinomial logistic regression. The findings show that women who share household choices with their spouses were more likely to undertake postnatal care for their babies in either private or public hospitals compared to self-medication/others/traditional. Also, women who owned houses and those who participate in economic activities are significantly more inclined to use postnatal services for babies in health facilities. By implication, women empowerment is a significant factor to consider in improving childcare services in Nigeria. This suggests that in order to improve the health of children, womens inputs in household decision-making should be accommodated, while efforts should be made to enhance household socioeconomic position, and support mothers to have formal education. The findings also suggest that promoting women's empowerment can play a crucial role in increasing the demand for formal childcare services. 2023, Women's Health and Action Research Centre. All rights reserved.